DESAIN MODEL MINIATUR MESIN CETAK PLASTIK INJEKSI SEBAGAI ALAT BANTU AJAR MATA KULIAH PLASTIK MOULDING DENGAN PENDEKATAN METODE KANO DAN QUALITY FUNCTION DEPLOYMENT (QFD) - Etik Puspitasari (Universitas Lambung Mangkurat, 2018)
Injection molding is the process of printing plastic products that are commonlyused for thermoplastic plastic materials. The working principle of this process isthat the plastic material is heated in a container called a barrel until it reaches itsmelting temperature. Then the material is injected into the print cavity to the brim.Once full, the plastic goods are cooled and ready to be released from the mold.The background of the researchers taking this study was because researchers wereeager to make miniature injection molding machines to be used as teachingmaterials in theory classes so that the lecturers could explain directly thecomponents and workings of injection molding machines in real terms not justimages or videos. The design of miniature models of plastic injection moldingmachines as teaching aids for molding plastic courses uses the canoe methodapproach and Quality Function Deployment (QFD). From the results of theKANO method approach obtained from 11 statement attributes of all attributesincluded in the Must Be category. None of the attributes entered the Indefferentcategory. Then the results of the KANO model correlation with Quality FuntionDeployment (QFD) are known as the priority sequence of attributes in the targetspecifications that will be used for product design. highest priority at House ofQuality (HOQ). And the final stage of the target specifications obtained can bemade of miniature injection molding machines which are used as teaching aids forplastic molding courses.